Assessing the Effect of Including Social Costs in Economic Evaluations of Diabetes-Related Interventions: A Systematic Review - Rodriguez-Sanchez B; Aranda-Reneo I; Oliva-Moreno J; Lopez-Bastida J (Dove Medical Press, 2021)
Beatriz Rodriguez-Sanchez,1 Isaac Aranda-Reneo,2 Juan Oliva-Moreno,3 Julio Lopez-Bastida4 1University Camilo José Cela, Faculty of Communication and Humanities, Madrid, Spain; 2University of Castilla-La Mancha, Faculty of Social Science, Economics and Finance Department, Toledo, Spain; 3University of Castilla-La Mancha, Faculty of Law and Social Science, Economics and Finance Department, Toledo, Spain; 4University of Castilla-La Mancha, Faculty of Health Sciences, Talavera de la Reina, Toledo, SpainCorrespondence: Beatriz Rodriguez-SanchezUniversity Camilo José Cela, Faculty of Communication and Humanities, Urb. Villafranca del Castillo, Calle Castillo de Alarcón, 49, Villanueva de la Cañada, Madrid, 28692, SpainEmail brodriguez@ucjc.eduBackground: The economic burden of diabetes from a societal perspective is well documented in the cost-of-illness literature. However, the effect of considering social costs in the results and conclusions of economic evaluations of diabetes-related interventions remains unknown.Objective: To investigate whether the inclusion of social costs (productivity losses and/or informal care) might change the results and conclusions of economic evaluations of diabetes-related interventions.Methods: A systematic review was designed and launched on Medline and the Cost-Effectiveness Analysis Registry from the University of Tufts, from the year 2000 until 2018. Included studies had to fulfil the following criteria: i) being an original study published in a scientific journal, ii) being an economic evaluation of an intervention on diabetes, iii) including social costs, iv) being written in English, v) using quality-adjusted life years as outcome, and vi) separating the results according to the perspective applied.Results: From the 691 records identified, 47 studies (6.8%) were selected. Productivity losses were included in 45 of the selected articles (73% used the human capital approach) whereas informal care costs in only 13 (when stated, the opportunity cost method was used in seven studies and the replacement cost in one). The 47 studies resulted in 110 economic evaluation estimations. The inclusion of social costs changed the conclusions in 8 estimations (17%), 6 of them switching from not cost-effective from the healthcare perspective to cost-effective or dominant from the societal perspective. Considering social costs altered the results from cost-effective to dominant in 9 estimations (19%).Conclusion: When social costs are considered, the results and conclusions of economic evaluations performed in diabetes-related interventions can alter. Wide methodological variations have been observed, which limit the comparability of studies and advocate for the inclusion of a wider perspective via the consideration of social costs in economic evaluations and methodological guidelines relating to their estimation and valuation.Keywords: diabetes, social costs, informal care, productivity losses, economic evaluation, health technology assessment